Nutritional strategies to modulate the adaptive response to endurance training - Hawley, J. A. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
In recent years, advances in molecular biology have allowed scientists to elucidate how endurance exercise training stimulates skeletal muscle remodeling (i.e. promotes mitochondrial biogenesis). A growing field of interest directly arising from our understanding of the molecular bases of training adaptation is how nutrient availability can alter the regulation of many contraction-induced events in muscle in response to endurance exercise. Acutely manipulating substrate availability can exert profound effects on muscle energy stores and patterns of fuel metabolism during exercise, as well as many processes activating gene expression and cell signaling. Accordingly, such interventions when repeated over weeks and months have the potential to modulate numerous adaptive processes in skeletal muscle that ultimately drive the phenotype-specific characteristics observed in highly trained athletes. In this review, the molecular and cellular events that occur in skeletal muscle during and after endurance exercise are discussed and evidence provided to demonstrate that nutrient availability plays an important role in modulating many of the adaptive responses to training. Emphasis is on human studies that have determined the regulatory role of muscle glycogen availability on cell metabolism, endurance training capacity and performance.